Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1137/17m1150426
|View full text |Cite
|
Sign up to set email alerts
|

Infinite-Dimensional Lur'e Systems: Input-To-State Stability and Convergence Properties

Abstract: We consider forced Lur'e systems in which the linear dynamic component is an infinite-dimensional well-posed system. Numerous physically motivated delay-and partial-differential equations are known to belong to this class of infinitedimensional systems. We investigate input-to-state stability (ISS) and incremental ISS properties: our results are reminiscent of well-known absolute stability criteria such as the complex Aizerman conjecture and the circle criterion. The incremental ISS results are used to derive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…This is combined in the notion of input-to-state stability (ISS), which has recently been studied for infinite-dimensional systems e.g. in [7,9,19,20] and particularly for semilinear systems in [5,6,23], see also [18] for a survey. The effect of feedback laws acting (approximately) linearly only locally is known in the literature as saturation and first appeared in [24,25] in the context of stabilization of infinite-dimensional linear systems, see also [10].…”
Section: Introductionmentioning
confidence: 99%
“…This is combined in the notion of input-to-state stability (ISS), which has recently been studied for infinite-dimensional systems e.g. in [7,9,19,20] and particularly for semilinear systems in [5,6,23], see also [18] for a survey. The effect of feedback laws acting (approximately) linearly only locally is known in the literature as saturation and first appeared in [24,25] in the context of stabilization of infinite-dimensional linear systems, see also [10].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to stability properties, our main result is Theorem 3.4, which is reminiscent of the complex Aizerman conjecture [19,20] (familiar from finite-dimensional control theory) and constitutes a refinement of [16,Theorem 4.1]. The main novelty here is that we obtain an incremental ISS estimate which is in terms of the Stepanov norm…”
Section: Introductionmentioning
confidence: 89%
“…We remark that the concept of almost periodicity in the sense of Stepanov generalizes that of Bohr, which, in the following, will be simply referred to as almost periodicity. Adopting the set-up considered in [16], we study the forced Lur'e system shown in Fig. 1, where Σ is a well-posed 1 linear infinite-dimensional system and f is a static nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations